PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING - Tias Penget Wigati (Neraca, 2020)
Profit is a measure of the success of the company's management performance in determining policies to be taken by the company related to operational activities in order to obtain maximum profit. Earnings growth can be predicted and measured its development from year to year by comparing the profits obtained today with the profits earned in the previous period. There are several factors that can affect earnings growth, namely the current ratio, debt to equity ratio, total asset turnover, sales growth, and company size. The object of this research is the coal mining sub-sector company listed on the Indonesia Stock Exchange Period 2016-2018. Data collection techniques using sampling techniques based on certain criteria. The number of samples used in this study is based on 23 criteria of the coal mining sub-sector companies. The analysis used in this study is Multiple Regression Analysis and Moderated Regression Analysis (MRA). The results of data analysis show that the debt to equity ratio has a negative effect on earnings growth. Total assets turnover has a positive effect on earnings growth. While the current ratio and sales growth does not affect profit growth. Then firm size strengthens the relationship between current ratio, debt to equity ratio, total asset turnover, and sales growth to profit growth